2011
DOI: 10.1021/bi2006866
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Biochemical Studies of the Hedamycin Type II Polyketide Ketoreductase (HedKR): Molecular Basis of Stereo- and Regiospecificities

Abstract: Bacterial aromatic polyketides that include many antibiotic and antitumor therapeutics are biosynthesized by the type II polyketide synthase (PKS), which consists of 5 – 10 stand-alone enzymatic domains. Hedamycin, an antitumor antibiotic polyketide, is uniquely primed with a hexadienyl group generated by a type I PKS followed by coupling to a downstream type II PKS to biosynthesize a 24-carbon polyketide, whose C9 position is reduced by hedamycin type II ketoreductase (hedKR). HedKR is homologous to the actin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 41 publications
2
42
0
Order By: Relevance
“…Aside from inactivation studies [47], stereospecificity of reductive domains has also been altered to produce analogs with different stereochemistry [48,49]. However, a complete understanding of the molecular basis for stereocontrol is still missing [50,51]. Directed evolution approaches that use small molecule surrogates of the usually ACP-tethered intermediates [52] may be better suited to identify stereochemistry-determining residues both proximal and distal to the ketoreductase (KR) active site.…”
Section: Other Pks and Nrps Functionsmentioning
confidence: 99%
“…Aside from inactivation studies [47], stereospecificity of reductive domains has also been altered to produce analogs with different stereochemistry [48,49]. However, a complete understanding of the molecular basis for stereocontrol is still missing [50,51]. Directed evolution approaches that use small molecule surrogates of the usually ACP-tethered intermediates [52] may be better suited to identify stereochemistry-determining residues both proximal and distal to the ketoreductase (KR) active site.…”
Section: Other Pks and Nrps Functionsmentioning
confidence: 99%
“…[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Enzymatically active KR domains are classified into A-type and B-type according to the stereochemistry of the β-hydroxyl group generated by ketoreduction. 26,[31][32][33][34][35][39][40][41] Signature motifs of the A-or B-type KR domains have been identified. However, because the signature motifs found in the KR domains of modular PKSs are usually absent in the KR domains of most PR-PKSs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Alignment of Iga13 with other KRs revealed that the canonical catalytic tetrad (Ser‐Tyr‐Lys‐Asn) of KR and the NAD(P)‐binding site are conserved in Iga13 (Figure S7). However, Iga13 lacks any motifs that have been reported to determine the stereospecificity of KRs (LDD motif in type I PKSs and PGG motif in type II PKSs) . We examined the activity of Iga13 toward 3‐oxooctanoyl‐ N ‐acetylcysteamine (NAC, 1 ; Figure a).…”
Section: Methodsmentioning
confidence: 99%